Evaluation of E-Mail Usage by Extended Technology Acceptance Model - Mutlu, Savaş; Efeoglu, İbrahim Efe (International Review of Management and Marketing, 2013)
This study is performed to evaluate E-mail usage by Extended Technology Acceptance Model (TAM2) and to test the moderation effects of Espoused National Cultural Values between Subjective Norm (SN) and E-mail usage Behavioral Intention (BI)/Perceived Usefulness (PU). Survey was conducted in Adana Branches of an important Turkish State-Run Bank including 151 participants who have E-mail access for work purposes. As the results of the study; PU and Perceived Ease Of Use (PEOU) have positive effects on BI, PEOU and SN both effect PU, Femininity (F) shows positive moderating effect on the relationship between SN and PU as well as the relation between SN and BI, Collectivism (C) shows positive moderation effect between SN and PU, moderation effect of SN on PU is higher for people who have higher tolerance to uncertainty. Keywords: E-mail Acceptance; Espoused National Cultural Values JEL Classifications: D83; M10